Ta có: \(\left(x+\sqrt{x^2+3}\right)\left(y+\sqrt{y^2+3}\right)=3\)
\(\Leftrightarrow\left(\sqrt{x^2+3}-x\right)\left(\sqrt{x^2+3}+x\right)\left(y+\sqrt{y^2+3}\right)=3\left(\sqrt{x^2+3}-x\right)\)
\(\Leftrightarrow3\left(y+\sqrt{y^2+3}\right)=3\left(\sqrt{x^2+3}-x\right)\)
\(\Leftrightarrow\left(y+\sqrt{y^2+3}\right)=\left(\sqrt{x^2+3}-x\right)\) (1)
Tương tự \(x+\sqrt{x^2+3}=\sqrt{y^2+3}-y\) (2)
Từ (1) (2) => x+y=0
làm bừa thui,ai tích mình mình tích lại
Số số hạng là :
Có số cặp là :
50 : 2 = 25 ( cặp )
Mỗi cặp có giá trị là :
99 - 97 = 2
Tổng dãy trên là :
25 x 2 = 50
Đáp số : 50